TreeSnap: A citizen science app connecting tree enthusiasts and forest scientists. Issue 1 (18th June 2019) - Crocker, Ellen; Condon, Bradford; Almsaeed, Abdullah; Jarret, Benjamin; Nelson, C. Dana; Abbott, Albert G.; Main, Doreen; Staton, Margaret
Societal Impact Statement: The scientists that study and work to improve forest health need information on where pests and diseases are spreading, as well as where healthy, resilient trees remain. TreeSnap is a citizen science project and mobile app created to meet this need by enabling citizens to easily submit global positioning system (GPS) locations, photos, and observational information about trees of interest to scientists. The app was designed and built to ensure that the data being collected directly helps scientists engaged in a number of forest health research activities, including studying the genetic diversity of tree species, breeding trees, and monitoring tree health. Abstract : The scientists that study and work to improve forest health need information on where pests and diseases are spreading, as well as where healthy, resilient trees remain. TreeSnap is a citizen science project and mobile app created to meet this need by enabling citizens to easily submit global positioning system (GPS) locations, photos, and observational information about trees of interest to scientists. The app was designed and built to ensure that the data being collected directly helps scientists engaged in a number of forest health research activities, including studying the genetic diversity of tree species, breeding trees, and monitoring tree health.